Purchase order for punch through concrete slab for the condensate drain pipe for each HAHU of the classroom for BracU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Modern Tech Enterprise for punch through concrete slab for condensate drain pipe for Brac University new campus project.